ASSESSMENT OF GENETIC VARIABILITY, HERITABILITY AND GENETIC ADVANCE AMONG TOMATO (SOLANUM LYCOPERSICUM L.) GERMPLASM - OM PRAKASH MEENA; VIJAY BAHADUR (The Bioscan, 2014)
The present investigation was carried out at Vegetable Research Farm, Department of Horticulture, SHIATS, Allahabad during 2012-13. The experiment was laid out in Randomized Block Design with three replications having thirty germplasm. Analysis of variance revealed significant differences among germplasm for all the traits studies, suggesting sufficient variability for yield and quality characters. The overall values of PCV were higher than those of GCV. Higher magnitude of GCV and PCV, respectively were recorded for leaf curl incidence per cent (35.45 and 35.46), followed by plant height, ascorbic acid and TSS ºBrix. High values of GCV are an indication of high genetic variability among the germplasm and thus the scope for improvement of these characters through simple selection would be better. In present study, all the characters showed high heritability the magnitude of heritability ranged from 92% to 100% indicating that these traits are controlled by additive gene action which is very useful in standard selection. The traits like plant height, leaf curl incidence per cent, TSS ºBrix and ascorbic acid with high GCV, PCV, heritability and genetic advance as percentage of mean, indicating that these characters are under additive gene effects and more reliable for effective selection.